Accumulation and biomass partition and nutrients per tropical ornamental plants grown in Ribeira Valley region - de Godoy, Leandro José Grava [UNESP]; Ferraz, Marcelo Vieira [UNESP]; da Silva, Lucas [UNESP]; Ferraz, Marcos Vieira [UNESP] (Lepidus Tecnologia, 2016)
For many ornamental plants there are no fertilization tables in Brazil and growers use, inappropriately, the same fertilizing for different species of ornamental plants. A first step is to know the nutrient uptake by these plants. The objective of this study was to determine the concentration and to characterize the accumulation of nutrients of the main tropical ornamental plants grown in the Ribeira Valley region, Sao Paulo state, Brazil: Clusia fluminensis, Dracaena marginata, Dypsis lutescens, Gardenia jasminoides, Ixora coccinea, Ligustrum sinense, Murraya paniculata, Podocarpus macrophyllus, Rhapis excelsa e Viburnum prunifolium. The plants were donated by local farmers and after sorting, these were divided into roots, stems and leaves, and, subsequently, washed, dried and was determined their concentration of nutrients. The experimental design was randomized using four repetitions and the species of ornamental plants were considered as treatments. The results were submitted to analysis of variance and compared by Scott-Knott test (5%). For the macronutrient, the greater accumulation of N was in Podocarpus macrophyllus. The Clusia fluminensis tree had the highest calcium and magnesium accumulations. The largest amounts of P and S were accumulated in Rhapis excelsa and Podocarpus macrophyllus. The greatest accumulation of K was in Rhapis excelsa, Dracaena marginata, Podocarpus macrophyllus, Murraya paniculata and Ixora coccinea. Smaller amounts of macronutrients were accumulated in Dypsis lutescens and Viburnum prunifolium. As for the macronutrients, the largest accumulation of Cu was observed in broad leaf Rhapis excelsa. Clusia fluminensis tree and Dracaena marginata accumulated the largest amounts of Mn. Regarding the Zn, Rhapis excelsa, Dracaena marginata and Ligustrum sinense were plants with higher accumulation. Smaller amounts of B were accumulated in Viburnum prunifolium, Dracaena marginata and Dypsis lutescens. Ligustrum sinense, Dypsis lutescens and Ixora coccinea accumulated lower amounts of Fe in relation to others. The accumulation of nutrients by ornamental plants is very different between species and this information should be used to adjust fertilizer recommendations. Ornamental plants were grouped as demand and NPK ratio, to assist in the management of fertilizer.
Keywords: Fertility; Fertilizing; Floriculture; Landscape; Nutrition